Muhammad Iqbal’s Pacifist Ethics and Global Peace in the Post-9/11 World - Saad Malook (Al Manhal Research Journal, 2023)
This article fosters the significance of Muhammad Iqbal’s pacifist ethics in the post-9/11 world. In the post-9/11, there emerged a new world order in which violence emerged in many guises, including terrorism and war, which has devastated global peace since the advent of the twenty-first century. Undeniably, the threat of a nuclear war has been constantly harassing the world. Under these atrocious conditions, the question is whether Iqbal’s pacifist ethics could help achieve and sustain global peace. Iqbal was an empirically informed and trained philosopher in the early twentieth century in the Western and Islamic traditions. He witnessed the First World War and identified the factors of the Second World War, which had started just a year after his death. Iqbal identified that materialistic interests and colonial and imperial exploitations cause conflicts, eventually leading to violence and war. The recurrent problem is how we avoid the Third World War to sustain global peace. Iqbal’s ethics offer two ideas for achieving global peace: reverence for humanity and human fraternity. Reverence for humanity helps develop human potential, which promotes creative activities vital for positive peace. Human fraternity is the only dependable unity among human beings, despite their particular races, colours, cultures, or languages, for acquiring global peace. The article thus demonstrates the relevance and significance of Iqbal’s ethics in achieving and sustaining a peaceful co-existence in the world.